Ferroptosis as a therapeutic target for inflammation-related intestinal diseases - Zhang, Xiaoli; Ma, Yiming; Lv, Guoqing; Wang, Hongying (Frontiers in Pharmacology, 2023)
Ferroptosis is an iron-dependent programmed cell death characterized by reactive oxygen species-induced lipid peroxidation and resultant membrane damage. Recent research has elucidated the mechanism of ferroptosis and investigated the relationship between ferroptosis and various diseases, including degenerative diseases, cancer, and inflammation. Ferroptosis is associated with inflammation-related intestinal diseases such as colitis and colitis-associated cancer. New insights into the role of ferroptosis in the pathogenesis of inflammation-related gut diseases have suggested novel therapeutic targets. In this review, we summarize current information on the molecular mechanisms of ferroptosis and describe its emerging role and therapeutic potential in inflammation-related intestinal diseases.